2015
DOI: 10.1186/s12883-015-0493-z
|View full text |Cite
|
Sign up to set email alerts
|

The ThRombolysis in UnconTrolled Hypertension (TRUTH) protocol: an observational study on treatment strategy of elevated blood pressure in stroke patients eligible for IVT

Abstract: BackgroundIntravenous thrombolysis (IVT) with (recombinant) tissue plasminogen activator is an effective treatment in acute ischemic stroke. However, IVT is contraindicated when blood pressure is above 185/110 mmHg, because of an increased risk on symptomatic intracranial hemorrhage. In current Dutch clinical practice, two distinct strategies are used in this situation. The active strategy comprises lowering blood pressure with antihypertensive agents below these thresholds to allow start of IVT. In the conser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The RIGHT-2 trial showed that functional outcomes were not improved with blood pressure reduction prior to stroke treatment (100). The Dutch ThRombolysis in Uncontrolled Hypertension (TRUTH) trial is an ongoing study evaluating whether actively lowering blood pressure below 185/110 mmHg affects stroke outcome in alteplase treated patients (101).…”
Section: Hypertension Treatment To Prevent Htmentioning
confidence: 99%
“…The RIGHT-2 trial showed that functional outcomes were not improved with blood pressure reduction prior to stroke treatment (100). The Dutch ThRombolysis in Uncontrolled Hypertension (TRUTH) trial is an ongoing study evaluating whether actively lowering blood pressure below 185/110 mmHg affects stroke outcome in alteplase treated patients (101).…”
Section: Hypertension Treatment To Prevent Htmentioning
confidence: 99%
“…Nevertheless, as the differences of stroke severities and pretreatment BP levels existed between groups, our results were still unable to answer the above questions. A randomized trial evaluating active BP-lowering strategies for acute ischemic stroke is in progress and may provide more evidences [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, as the differences of stroke severities and pretreatment BP levels existed between groups, our results were still unable to answer the above questions. A randomized trial evaluating active BP-lowering strategies for acute ischemic stroke is in progress and may provide more evidences [23,24]. Subgroup analysis according to stroke severity showed that admission BP excursion compromised thrombolysis effect in patients with severe stroke but not in those with moderate stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension may also modify the clinical outcome in patients undergoing a specific treatment of AIS. Available evidence shows that arterial hypertension is related to poor functional outcome after intravenous thrombolysis [104]. However, in a recently published multicentre study of ischemic stroke in patients eligible for intravenous thrombolysis (ENCHANTED study), hypertension favored neither guideline-recommended blood pressure lowering nor intensive blood pressure lowering [68••].…”
Section: Bp Management In Acute Ischemic Stroke Patients With and Witmentioning
confidence: 99%